Strategi Pengembangan Industri Halal di Indonesia Berbasis Maqashid Syari’ah dan Etika Bisnis Islami - Minarni, Minarni (Jurnal Ilmiah Ekonomi Islam, 2024)
The halal industry in Indonesia is on the rise. In Indonesia's sharia economic master plan, the government targets Indonesia to become a halal center by 2024. To realize this target, an appropriate halal industry development strategy is needed. Strength factors for developing the halal industry in Indonesia include a majority Muslim population, good regulations, wealth of natural resources, reliability of human resources, capital and entrepreneurial skills. This research aims to examine the development of the halal industry in Indonesia referring to the concept of maqashid syari'ah and Islamic business ethics. The study was carried out using literature research with qualitative descriptive methods and a normative approach. The research results show that the concept of maqashid shari'ah and Islamic business ethics are very important as guidelines in developing the halal industry in order to maintain compliance with Islamic values and ward off secular values. This research also shows that the internalization of maqashid sharia and Islamic business ethics in the halal industry is able to increase consumer confidence so that the halal industry obtains a strong position in business competition and has an impact on increasing the income of halal industry players and contributing to increasing national economic growth.